Predictive value of auscultation of femoropopliteal arteries (Swiss Medical Weekly, 2013)
Summary BACKGROUND: Femoropopliteal bruits indicate flow turbulences and increased blood flow velocity, usually caused by an atherosclerotic plaque or stenosis. No data exist on the quality of bruits as a means for quantifying the degree of stenosis. We therefore conducted a prospective observational study to investigate the sensitivity and specificity of femoropopliteal auscultation, differentiated on the basis of bruit quality, to detect and quantify clinically relevant stenoses in patients with symptomatic and asymptomatic peripheral arterial disease (PAD). METHODS: Patients with known chronic and stable PAD were recruited in the outpatient clinic. We included patients with known PAD and an ankle-brachial index (ABI)